Human trafficking from Shari'ah perpective - Mokhtar, Khairil Azmin; Ab Hamid, Zuraini (Serials Publications, 2014)
People thought slavery towards human has ended in the 19th century. However, despite the achievements of those 19th-century abolitionists, human trafficking has become the fastest growing criminal enterprise in the world where the syndicate has obtained about USD32 billion a year through the sale, abuse and exploitation of the victims. To curb the crime, the world needs an effective tool as guidance. Nowadays, international framework on human trafficking has become the main guiding framework for most of the countries around the world including the Islamic countries such as Malaysia. Other than the international framework, Islamic religion also has established its concern toward this issue. Therefore, this paper analyses the human trafficking perspective from the Islamic legal framework. This paper found that the Islamic religion has advanced its laws and principles on the prohibition of human trafficking, earlier than the international law or any national laws around the globe.